Réceptions de campagnes de communication publiques sur le risque volcanique - Lise Jacquez; Sébastien Rouquette (Communiquer)
Do public communication campaigns on volcanic risks succeed in raising the awareness of the inhabitants concerned? Do the latter know, thanks to these campaigns, the behaviors to adopt in case of eruption? From an empirical survey, this research studies the reception and the interpretation of awareness campaigns on the risks of the Misti volcano by the population of Arequipa. It aims to inform risk reduction policies by helping to evaluate the impact of the arguments, messages and images used during such campaigns. It also aims to estimate the degree of memorization and knowledge of the instructions of preparation given by the authorities and the factors that explain that a part of the inhabitants takes more into account this information than others (neighborhood, age, gender, previous experience of the risk, etc.).